Universal Scaling Law for Methane Capture Quantity in Metal–Organic Frameworks. Issue 4 (2nd January 2019) - Lin, Haoxiang; Cai, Shuhong; Zhu, Xi
Abstract: In this work, a universal scaling law for the methane gas capture quantity in metal–organic frameworks (MOFs) structure is provided. The methane–MOF adsorption events are catalogued into energy and space scenario individually. The energy factor includes three types of energy forces for both bonding and non‐bonding interactions in variant type of MOFs structures: that is, 1) metal–gas interactions, 2) heteroatom–gas bonds, and 3) non‐bonding interactions, including Van der Waals as well as Coulomb interactions. The subspace factor includes: 1) geometrical void fraction volume, 2) surface area, and 3) the limiting local pore size. Under this catalogue, more than 65 000 types of MOFs with relative high gas capture are studied; a linear scaling law can be approached via the group combination of the energy and space factor. Moreover, the decomposed scaling law indicates that for the exploring of high gas storage MOFs structure, the design of spatial geometry takes more importance than the chemical bonding of gas–MOFs interactions. The linear scaling works for other gases, like nitrogen and carbon dioxide as well. This work provides a qualitative understanding for the design of MOFs materials for the gas capture utility. Abstract : The universal scaling of the gas adsorption in MOF structures is achieved by combining the energy factor between the gas–MOF interaction and the space factor, including void fraction, surface areas, and pore size. This scaling can work well for methane, nitrogen, and carbon dioxide gas; provides a qualitative understanding for the design of MOFs materials with gas capture utility.